2014
DOI: 10.3109/0284186x.2014.927074
|View full text |Cite
|
Sign up to set email alerts
|

Early interim PET/CT predicts post-treatment response in diffuse large B-cell lymphoma

Abstract: SUVmax is more accurate to detect tumor aggressiveness than biopsy in DLBCL, since BmSUVmax represents the most aggressive tumor of the patient. Interim PET/CT as early as one week after R-CHOP therapy predicts response. Thus, it could be used as a tool for guidance of risk stratification in DLBCL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Previous studies suggested that a low MTV on I-PET or a major decrease of MTV vs. baseline PET in DLBCL, predicts response at end-of-treatment PET and progression-free-survival (7-9,15-17). However, MTV cut-offs were different, and it is unclear whether and/or to which extent this relates to the use of different semi-automated delineation algorithms; Oñate-Ocaña used a 40%SUVmax threshold, Zhang a 41%, Wu a 42% and Malek a 37%SUVmax threshold and a gradient-based segmentation method (Gradient), while Islam applied a SUV4.0 threshold and Yang and Mikhaeel a SUV2.5 threshold (7)(8)(9)(15)(16)(17)34). This precludes any meaningful meta-analysis to build the case of evidence for MTV as a predictor for clinical outcome additional to (delta)SUVmax and the five-point DS (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that a low MTV on I-PET or a major decrease of MTV vs. baseline PET in DLBCL, predicts response at end-of-treatment PET and progression-free-survival (7-9,15-17). However, MTV cut-offs were different, and it is unclear whether and/or to which extent this relates to the use of different semi-automated delineation algorithms; Oñate-Ocaña used a 40%SUVmax threshold, Zhang a 41%, Wu a 42% and Malek a 37%SUVmax threshold and a gradient-based segmentation method (Gradient), while Islam applied a SUV4.0 threshold and Yang and Mikhaeel a SUV2.5 threshold (7)(8)(9)(15)(16)(17)34). This precludes any meaningful meta-analysis to build the case of evidence for MTV as a predictor for clinical outcome additional to (delta)SUVmax and the five-point DS (10,11).…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has reported that interim treatment response to first-line chemotherapy acts as an important prognostic factor in DLBCL patients. Patients with poor interim treatment response and positive interim PET are more likely to have recurrence and progression, and the prognosis generally remains worsened (26)(27)(28)(29). Poor interim treatment response is an indication for early clinical intervention, including salvage treatment, intensive treatment or autologous stem cell transplantation (30).…”
Section: Discussionmentioning
confidence: 99%
“…PET allows target adjustment due to volume changes in response to chemotherapy (adaptive planning) during treatment. More importantly, PET-CT provides excellent post-treatment evaluation, especially in patients with HL and DLBCL [36,37]. Although the clinical benefits may be less apparent for other lymphomas, PET-CT is considered the state-of-the-art imaging technique and the most sensitive and specific functional imaging currently available for the assessment of lymphoma and many other malignancies [26].…”
Section: Lymphoma Imagingmentioning
confidence: 99%